2001
DOI: 10.29173/slw7098
|View full text |Cite
|
Sign up to set email alerts
|

An International Study on Principal Influence and Information Services in Schools: Synergy in Theme and Methods

Abstract: Support of the principal is a key factor in the implementation of effective programs in schools, An international study of the principal's role in developing and supporting school library programs was conducted in Australia, Canada, Finland, France, Japan, Scotland, and South Korea. The purpose of the study was to provide information, for principals and teacher-librarians in countries throughout the world that might inform their efforts to develop information-literate school communities. Principals and teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This might be done through publication of newsletters, pamphlets posters banners among others. The finding of this study is in support of Henri, Hay and Oberg (2002), who indicated that by utilizing all the tools of promotion, marketing and public relations in any advocacy activity a librarian is able to build a working relationship with clienteles to identify and agree to some common elements in respect to the role and function of the library and its personnel and services. Also, the finding of this study is in support of the findings of Ayanda and Taiwo (2008) who conducted a study on the impact of advocacy on library management, a marketing perspective and found out a significant impact of advocacy on library marketing.…”
Section: Advocacy and Students' Patronage Of Information Servicessupporting
confidence: 69%
“…This might be done through publication of newsletters, pamphlets posters banners among others. The finding of this study is in support of Henri, Hay and Oberg (2002), who indicated that by utilizing all the tools of promotion, marketing and public relations in any advocacy activity a librarian is able to build a working relationship with clienteles to identify and agree to some common elements in respect to the role and function of the library and its personnel and services. Also, the finding of this study is in support of the findings of Ayanda and Taiwo (2008) who conducted a study on the impact of advocacy on library management, a marketing perspective and found out a significant impact of advocacy on library marketing.…”
Section: Advocacy and Students' Patronage Of Information Servicessupporting
confidence: 69%
“…• manage$the$school$library$ • plan,$implement$and$evaluate$and$their$teaching$and$library$programs$$ • raise$awareness$of$their$potential$impact$on$student$learning$and$literacy$$ No$ matter$ how$ many$ 'busy'$ activities$ teacher4librarians$ undertake,$ the$ value$ of$ their$ role$ is$ most$ clearly$ demonstrated$ by$ learning$ and$ literacy$ outcomes.$ $ By$ using$ evidence$ about$ the$ school's$ learning$ and$ teaching$ needs,$ teacher4librarians$ can$ align$ their$ school$ library$ vision$ and$ objectives$ with$ those$ of$ the$ school$ leadership$ team$ $ Shannon,$ 2012).$ By$ evaluating$ their$ teaching$ and$ library$ programs,$ teacher4librarians$ gain$ further$ evidence$ to$ guide$ their$ practice$ and$ inform$ the$ leadership$ team.$ In$ this$ way,$ they$ can$ demonstrate$ their$ practical$ impact$ on$ educational$ and$ social$ outcomes$ throughout$ the$ school$ (Ash4Argyle$ &$ Shoham,$ 2012;$ Everhart,$2006;$Hay$&$Todd,$2010).$$ Evidence$ often$ becomes$ more$ useful$ as$ a$ shared$ resource.$ By$ developing$ collaborative$ partnerships$ with$ teaching$ colleagues$ and$ principals,$ teacher4librarians$ can$ gather$ and$ disseminate$ evidence$ (Everhart,$ 2006;$ Hartzell,$ 2002;$ Henri,$ Hay,$ &$ Oberg,$ 2002;$ Oberg,$ 2006;$ Shannon,$ 2012;$ Small,$ Shanahan,$ &$ Stasak,$ 2010).$ Through$ collaboration,$ teacher4librarians$ gain$ useful$ information$ about$ school$ issues.$ Meanwhile$ teachers$ and$ principals$ will$ develop$ understanding$ of$ information$ policy$ issues$ affecting$ teachers$ and$ students,$ such$ as$ cybersafety$ In$addition$to$carrying$out$practical$investigations,$evidence$based$practitioners$can$draw$ on$the$literature$to$research$different$theoretical$models$or$exemplary$case$studies.$Recommended$ Australian$resources$include:$…”
Section: Demonstrating the Differencementioning
confidence: 99%
“…Eight of the total 153 articles (5%) were co-authored by researchers from two different countries. Six of these projects took place in each of their respective countries (Everhart, Dresang, & Kotrla, 2005;Hell, Engstrom, & Lundgren, 2003;Henri, Lee, & Chan, 2006;Henri, et al, 2003;Kong, Lee, F., Li, & Lee, S., 2005), and two took place in the researchers' home countries as well as in other countries (Farmer, 2007;Henri, Hay, & Oberg, 2002). These can be regarded as international studies in that the gaze extended beyond individual nations to several-from two to seven.…”
Section: Figure 2 Publications By Authors In Emerging Countries (N=12)mentioning
confidence: 99%